Bioinformatics Analysis Identifies Potential Related Genes in the Pathogenesis of Intrauterine Fetal Growth Retardation. (July 2022) - Xiao, Chao; Wang, Yao; Fan, Yuchao
Background: Intrauterine growth retardation (IUGR) affects approximately 10% to 15% of all pregnancies worldwide. IUGR is not only associated with stillbirth and newborn death, but also the delay of cognition in childhood and the promotion of metabolic and vascular disorders in adulthood. Figuring out the mechanism of IUGR is rather meaningful and valuable. Methods: Datasets related to IUGR were searched in the Gene Expression Omnibus website. Principal component analysis (PCA) was used for normalization. Differential expressed genes (DEGs) were screened out using the ggpot2 tool. DEGs were used to conduct Gene Ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analyses, and protein-protein interaction (PPI) analysis. IUGR related genes were searched in the OMIM website to look for the intersection with the DEGs. The DEGs were analyzed for tissue-specific expression by the online resource BioGPS. The results were displayed through volcano map, Venn map, box plot, heat map, and GSEA enrichment plots drawn by R language packages. Results: Eleven DEGs were screened out of 2 datasets. One hundred ninety-five genes related to IUGR in OMIM were retrieved. EGR2 was the only intersection gene that was found in both groups. Genes associated with placental tissue expression include COL17A1, HSD11B1, and LGALS14. Molecular functions of the DEGs are related to the oxidoreductase activity. The following 4 signaling pathways, reactome signaling by interleukins, reactome collagen degradation, Naba secreted factors, and PID NFAT tfpathway, were enriched by GSEA. Two critical modules comprising 5 up-regulated genes (LEP, PRL, TAC3, MMP14, and ADAMTS4) and 4 down-regulated genes (TIMP4, FOS, CCK, and KISS1) were identified by PPI analysis. Finally, we identified 6 genes (PRL, LGALS14, EGR2, TAC3, LEP, and KISS1) that are potentially relevant to the pathophysiology of IUGR. Conclusion: The candidate down-regulated genes LGALS14 and KISS1, as well as the up-regulated genes PRL, EGR2, TAC3, and LEP, were found to be closely related to IUGR by bioinformatics analysis. These hub genes are related to hypoxia and oxidoreductase activities in placental development. We provide useful and novel information to explore the potential mechanism of IUGR and make efforts to the prevention of IUGR.